Dampak penerapan protokol kesehatan Coronavirus disease (COVID-19) mencuci tangan terhadap kualitas air permukaan Kota Palangkaraya pada era new normal - Dhymas Sulistyono Putro; Achmad Imam Santoso (Universitas Riau, 2022)
Palangka Raya City is one of the cities affected by COVID-19, where on November 11, 2021, and 13104 people were confirmed positive for COVID-19. The Health Protocol continues to be carried out in this New Normal era. The Health Protocol by washing hands with soap is an environmental issue that needs attention, namely the use of hand soap which reduces surface air quality. Hand soap contains chemicals that can increase the concentration of Chemical Oxygen Demand (COD). There is a need for laboratory testing of the COD parameters of surface water around handwashing facilities in public facilities in the era of new habits. The research was divided into laboratory tests on surface water parameters, namely pH, temperature, and COD as well as field surveys on the use of handwashing facility. The results of laboratory tests show that the quality of surface water on the COD parameter is below the quality standard. The use of handwashing facilities is not justified, because its use is only 19%. Along with the low use of handwashing facilities, hand washing facilities do not have an impact on decreasing surface water quality on the COD parameter, it can be an action to maintain surface water quality.